Screening and outcomes of co-occurring traumatic brain injury among people with spinal cord injury: a scoping review - Deborah L. Snell; Phoebe Wynands; Jennifer Dunn; Joanne Nunnerley; Alice Theadom (Journal of Rehabilitation Medicine)
Objective: To map existing knowledge on screening and rehabilitation outcomes for co-occurring traumatic brain injury among people with traumatic spinal cord injury (SCI).